Do In-School Feeding Programs Have an Impact on Academic Performance and Dropouts? The Case of Public Schools in Argentina. - Adrogue, Cecilia; Orlicki, Maria Eugenia (Education Policy Analysis Archives, 2013)
As Argentina presents problems of malnutrition, the federal in-school feeding program has become a key policy because it provides an important nutritional intervention during a relevant growth period.  This paper estimates the effect of the program on academic performance -measured by standardized test scores- with a difference in difference model which exploits the change over time in the supply of the in-school feeding program during the end of the nineties. We build an original panel using the ONEE corresponding to the years 1997, 1999 and 2000. Our findings suggest that the program has successfully targeted the most disadvantaged schools. However, only partial improvement in school performance has been found. Language test scores were the only ones to show a statistically significant improvement, with no noticeable effects reported in math scores. These results are consistent with the characteristics of the federal in-school feeding program in Argentina, which do not compensate for the nutritional deficit the children bring from their homes. This implies that having an in-school feeding program –even that reaching the most needy populations- does not necessarily address the desired goals of compensating for nutritional deficits and correlating to improved test results for students.